Diversity and Low Parasitism of Egg Parasitoids Associated with Maize (Zea mays) in Madura, Indonesia - Panca Ayu Virgirl; Wiwin Windriyanti; Ramadhani Mahendra Kusuma (The University of Lampung, 2026)
This study aimed to explore and identify egg parasitoids associated with maize (Zea mays) in Keleyan Village, Bangkalan Regency, Madura. Field observations were conducted during both vegetative and generative growth stages using a direct survey method. Eggs of lepidopteran pests were collected and reared under laboratory conditions to observe the emergence of adult parasitoids. The results showed that only one genus of egg parasitoid was found, namely Trichogramma spp., which parasitized the eggs of Spodoptera frugiperda at a parasitism rate of 17.3%. This rate was low for a biological control program. These findings indicate that the presence of natural parasitoids in the study area was not sufficiently effective in suppressing pest populations under natural conditions. Nevertheless, Trichogramma spp. still shows potential as a biological control agent, particularly if supported by augmentative or conservation-based approaches. This results can be used as foundation for the development of ecological-based environmentally friendly, and sustainable pest control strategies in lowland maize cultivation systems, especially in the Madura region.